The DVB Channel Coding Application Using the DSP Development Board MDS TM-13 IREF - Kratochvil, Tomas; Slanina, Martin (Radioengineering Society, 2004)
The paper deals with the implementation of the channel coding according to DVB standard on DSP development board MDS TM-13 IREF and PC. The board is based on Philips Nexperia media processor and integrates hardware video ADC and DAC. The program libraries features used for MPEG based video compression are outlined and then the algorithms of channel decoding (FEC protection against errors) are presented including the flowchart diagrams. The paper presents the partial hardware implementation of the simulation system that covers selected phenomena of DVB baseband processing and it is used for real time interactive demonstration of error protection influence on transmitted digital video in laboratory and education.
Keywords: Digital video; digital television; channel coding; for-ward error correction; MPEG; Nexperia DSP